Modelling Paper Microstructure and its Role in Toner Transfer in Xerographic Printing - Wu, Tao (My University, 2008)
This thesis investigates paper structure and how its spatial heterogeneity affects the electrostatic and contact forces responsible for the toner transfer in Xerographic printing. Modeling predictions and experiments are reported which link length scales of variation in toner density distribution in Xerographic printing with certain structural length scales in paper.
A modified 3D fibre network model is introduced, which is used to simulate handsheet paper microstructure. Specific measures addressed by the model include formation, surface roughness and porosity. Simulated (i.e. virtual) handsheet paper structure is compared with that from specially prepared laboratory handsheet, obtaining a good correspondence between theory and experiments.
An efficient Multigrid Poisson solver is used to simulate the electrostatic fields involved in the Xerographic toner transfer process. The distribution of dielectric property is input into the solver either analytically or from simulated 3D paper webs prepared by the fibre network model of paper. A spectral analysis is used to elucidate the relative importance of spatial variations of paper surface, filler and porosity in establishing spatial variations of the electrostatic field. It is found that only long wavelength variations in either surface height, bulk filler or porosity affect variations in electrostatic toner transfer forces to any relevant degree. Furthermore, it is shown that the long wavelength perturbations of the electrostatic field can be modeled using a new 1D effective capacitor model. Direct use of simulated handsheet paper webs - which are described by several heterogeneous measures - shows that to lowest order it is the paper surface structure not formation is responsible in shaping the electrostatic toner field variations.
A new platform for modeling toner transfer in Xerographic printing is also introduced. It combines the 3D stochastic fibre network model of paper, the 3D electrostatic field solver, paper compression in the printing nip, and contact adhesion forces acting on toner particles during Xerographic printing. The modeling platform is used to demonstrate that paper-press interactions are critical in shaping the surface of paper, which, in turn, has the greatest influence in controlling both the electrostatic and contact adhesion forces responsible for shaping the distribution of toner transferred to paper during Xerography.
Keywords: paper structure, spatial heterogeneity, toner, transfer, Xerographic, 3D fibre network